Utilization of Solar Powered Water Pump System to Support Fish Cultivation : Pemanfaatan Sistem Pompa Air Tenaga Surya untuk Pendukung Budidaya Ikan - Sa'adah, Nihayatus; Sudibyo, Rahardhita Widyatra; Nadziroh, Faridatun; Mahmudah, Hani’ah; Budikarso, Anang; Siswandari, Nur Adi; Milchan, Muhammad; Santoso, Djoko; Ratri, Aestatica; Firmansyah, Ferdiaz; Tasya, Salsabila; Maharani, Ellsa Christy (Universitas Lancang Kuning, 2024)
Maintaining water quality in fish ponds is crucial in aquaculture. Fish farmers strive to increase yields by improving water circulation, temperature, and pH levels in the ponds. Poor water circulation can lead to significant pH changes and disrupt the health and growth of the fish. In some areas, farmers use electrically powered water pumps for water circulation. For a more environmentally friendly solution, innovation in water pump design is needed. The proposed appropriate technology is a solar-powered water pump, which uses solar panels as the electricity source. Test results show that the solar panel can fully charge the battery from 7:00 AM to 5:00 PM. Testing of the DS18B20 temperature sensor shows good accuracy with a maximum error of 1.47%, while the pH sensor also works quite accurately with a maximum error of 1.8%, making them suitable for monitoring water quality in fish farming.